Pharmacologically Inactive Bisphosphonates as an Alternative Strategy for Targeting Osteoclasts: In Vivo Assessment of 5‐Fluorodeoxyuridine‐Alendronate in a Preclinical Model of Breast Cancer Bone Metastases. (7th November 2016) - Schem, Christian; Tower, Robert J; Kneissl, Philipp; Rambow, Anna‐Christina; Campbell, Graeme M; Desel, Christine; Damm, Timo; Heilmann, Thorsten; Fuchs, Sabine; Zuhayra, Maaz; Trauzold, Anna; Glüer, Claus C; et al.
ABSTRACT: Bisphosphonates have effects that are antiresorptive, antitumor, and antiapoptotic to osteoblasts and osteocytes, but an effective means of eliciting these multiple activities in the treatment of bone metastases has not been identified. Antimetabolite‐bisphosphonate conjugates have potential for improved performance as a class of bone‐specific antineoplastic drugs. The primary objective of the study was to determine whether an antimetabolite‐bisphosphonate conjugate will preserve bone formation concomitant with antiresorptive and antitumor activity. 5‐FdU‐ale, a highly stable conjugate between the antimetabolite 5‐fluoro‐2'‐deoxyuridine and the bisphosphonate alendronate, was tested for its therapeutic efficacy in a mouse model of MDA‐MB231 breast cancer bone metastases. In vitro testing revealed osteoclasts to be highly sensitive to 5‐FdU‐ale. In contrast, osteoblasts had significantly reduced sensitivity. Tumor cells were resistant in vitro but in vivo tumor burden was nevertheless significantly reduced compared with untreated mice. Sensitivity to 5‐FdU‐ale was not mediated through inhibition of farnesyl diphosphate synthase activity, but cell cycle arrest was observed. Although serum tartrate‐resistant acid phosphatase (TRAP) levels were greatly reduced by both drugs, there was no significant decrease in the serum bone formation marker osteocalcin with 5‐FdU‐ale treatment. In contrast, there was more than a fivefold decrease in serum osteocalcin levels with alendronate treatment ( p < 0.001). This finding is supported by time‐lapse micro–computed tomography analyses, which revealed bone formation volume to be on average 1.6‐fold higher with 5‐FdU‐ale treatment compared with alendronate ( p < 0.001). We conclude that 5‐FdU‐ale, which is a poor prenylation inhibitor but maintains potent antiresorptive activity, does not reduce bone formation and has cytostatic antitumor efficacy. These results document that conjugation of an antimetabolite with bisphosphonates offers flexibility in creating potent bone‐targeting drugs with cytostatic, bone protection properties that show limited nephrotoxicity. This unique class of drugs may offer distinct advantages in the setting of targeted adjuvant therapy and chemoprevention of bone diseases. © 2016 American Society for Bone and Mineral Research.